2018
DOI: 10.1155/2018/7569809
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Polymorphisms of NLRP3 Inflammasome Associated with T Helper Cells in Patients with Multiple Myeloma

Abstract: The pathogenesis of multiple myeloma (MM) remains unclear and the NLRP3 inflammasome has been more and more recognized in the progression of many diseases. To investigate the role of the NLRP3 inflammasome in MM, we determined the genetic polymorphisms and expression of NLRP3 inflammasome-related genes (IL-1β, IL-18, CARD8, and NF-κB) in MM patients, and explored their clinical relevance. Furthermore, we investigated the relationship of the NLRP3 inflammasome with Th cells in MM. Our study showed that the CARD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…A recent study described a possible role of the NLRP3 inflammasome and its downstream cytokines in the development of myeloma [325]; such a role in myeloma pathogenesis for the cytokine network and immunocompetent cells has also been suggested by immunogenetic studies [326]. These observations further suggest that immunocompetent cells, immunogenetic factors, or both are involved in the pathogenesis of multiple myeloma.…”
Section: The Plasma Cell Population In Multiple Myelomamentioning
confidence: 89%
“…A recent study described a possible role of the NLRP3 inflammasome and its downstream cytokines in the development of myeloma [325]; such a role in myeloma pathogenesis for the cytokine network and immunocompetent cells has also been suggested by immunogenetic studies [326]. These observations further suggest that immunocompetent cells, immunogenetic factors, or both are involved in the pathogenesis of multiple myeloma.…”
Section: The Plasma Cell Population In Multiple Myelomamentioning
confidence: 89%
“…Some other studies more broadly have implicated the NLRP3 inflammasome in cancer and links to proliferation of T cells/lymphoma cells. In multiple myeloma patients with a mutation in CARD8 (a negative regulator of NLRP3 inflammasome) had a significantly higher percentage of pro-inflammatory Th1 cells (37). Another study from the same group has shown that NLRP3 inflammasome activation promoted lymphoma cells proliferation and inhibited apoptosis through up-regulation of c-myc and bcl-2 anti-apoptotic factors (38).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, antagonists, such as small molecules or antibodies targeting components of the inflammasome complex are developed (9,27). Our previous studies also demonstrated that the polymorphisms of NLRP3 inflammasome might be involved in the pathogenesis of hematological malignancies, such as lymphoma (28), multiple myeloma (29), myelodysplastic syndromes (30) and AML (31). Moreover, we found that aberrant NLRP3 expression associated with Aryl hydrocarbon receptor (AHR) may contribute to Th cells imbalance in AML patients (3).…”
Section: Introductionmentioning
confidence: 95%